The Correlation Between the Types of Initial Bacterial Infection and Clinical Prognosis in Patients With Septic AKI - Li, Tian; Liu, Jing yuan; Liu, Jing feng; Duan, Meili; Li, Ang (Frontiers in Medicine, 2022)
Background: Acute kidney injury (AKI) is a common complication of sepsis and is an independent risk factor for mortality. It is unclear whether different bacteria play different roles in the occurrence and development of sepsis-associated acute kidney injury(S-AKI). We observed the clinical characteristics and outcomes of patients that the types of bacterial infection, and different infections sites before the occurrence of AKI respectively. Methods: Data of patients who were diagnosed with sepsis and later developed acute kidney injury from 2008 to 2019 were retrieved from the MIMIC-IV 1.0 database. Patients were first divided into two groups according to the bacterial culture results obtained prior to AKI occurrence: bacterial cultured positive (N=1785) and bacterial cultured negative (N=8777). Patients with bacteria culture positive were divided into culture bacteria gram-positive (CGP, N=1248) and gram-negative (CGN, N=537) groups. Results: Overall, 1785 patients were included in the present analysis. The patients in CGN group were older (70 vs 66, P＜0.001), had lower BMI (27.0 vs 28.4, P＜0.001), higher acute physiology III (APS III) score (63.0 vs 58, P=0.001), shorter time from positive microbial culture to diagnosis of AKI (2.94 vs 3.16 days, P=0.013) and longer ICU stay time (5.94 vs 4.77 days, P＜0.001) compared to those in the CGP group (n=1248). In the CGNb group, the rate of vasopressors using (73.1% vs 56.4%, P=0.007), the SOFA score (10 vs 9, P=0.005) and the level of lactate (3.7 vs 2.5, P=0.001) were higher than those in the CGPb group. The time from positive microbial culture to diagnosis of AKI was shorter (2.23 vs 3 days, P=0.001) in the CGNb group. However, there was no significant difference in continuous renal replacement treatment (CRRT) application or short-term mortality rates between CGN and CGP groups. Conclusion: The gram types of bacteria cultured prior to S-AKI occurrence was not related to AKI stage, CRRT application, and short-term mortality. Compared with Gram-positive bacterial infections, Gram-negative bacterial infections take a shorter time to develop into AKI, and had a higher disease severity score.